100% Nitrous Oxide in the Oxygen Line: How Could This Happen in a Modern Anesthesia Machine?. Issue 3 (November 2020) - Joo, Sarah S.; Bechtold, Hannah; Jaffe, Richard A.; Brock-Utne, John G.
Abstract : The inadvertent crossover between O2 and N2 O pipelines has become extremely rare in practice. We describe a case where it was possible to ventilate with 100% N2 O instead of the intended 100% O2 on a modern anesthesia delivery system (Dräger Apollo; Drägerwerk AG & Co KgaA, Lübeck, Germany). This was the result of the incorrect assembly of diameter index safety system (DISS) components during preventative maintenance that defeated the DISS failsafe system. To make incorrect assembly easier to avoid, DISS component labeling could be more prominent and color-coded, or the internal construction of the gas manifold could incorporate DISS.